Woreda-level participatory land use planning for pastoral areas in Ethiopia - CGIAR Research Program on Policies, Institutions, and Markets (2019)
After the piloting stage and additional stakeholder consultations, the process was finalized and a manual produced. The manual was launched by the Ministry of Agriculture in 2019, followed by trainings.